Respuesta :

Answer:

7

Step-by-step explanation:

because 2 plus 4 plus 4 equals 9 and 9 minus 16 equals 7 so 7 is your answer.

Answer:

Answer: 2

Step-by-step explanation:

Simplifying

16 = 4 + 3(t + 2)

Reorder the terms:

16 = 4 + 3(2 + t)

16 = 4 + (2 * 3 + t * 3)

16 = 4 + (6 + 3t)

Combine like terms: 4 + 6 = 10

16 = 10 + 3t

Solving

16 = 10 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.

16 + -3t = 10 + 3t + -3t

Combine like terms: 3t + -3t = 0

16 + -3t = 10 + 0

16 + -3t = 10

Add '-16' to each side of the equation.

16 + -16 + -3t = 10 + -16

Combine like terms: 16 + -16 = 0

0 + -3t = 10 + -16

-3t = 10 + -16

Combine like terms: 10 + -16 = -6

-3t = -6

Divide each side by '-3'.

t = 2

Simplifying

t = 2